Ejaculate Traits and Sperm Morphology Depending on Ejaculate Volume in Duroc Boars - Górski, Krzysztof (J Vet Res, 2017)
INTRODUCTION: The aim of this study was to evaluate the dependence between ejaculate traits, sperm morphology, and ejaculate volume in Duroc boars. MATERIAL AND METHODS: The analysis involved 121 ejaculates collected from 12 Duroc boars kept in three artificial insemination centres located in central Poland. Ejaculates were collected manually at one-month intervals, over a period of 10 months. At least 10 ejaculates were collected from each boar. The material was divided by ejaculate volume and each ejaculate was assigned to one of three volume groups: 160 mL and lower, 161–200 mL, and 201 mL and higher. The ejaculates were assessed to identify the basic physical traits and determine the incidence of morphological abnormalities in the spermatozoa, specifying major and minor abnormalities. Furthermore, the morphological structure indices for the spermatozoa were also calculated. RESULTS: In large-volume ejaculates, spermatozoa were more elongated in shape, their heads were more elongated and had the largest flagella. With an increase in the ejaculate volume, sperm concentration in the ejaculate decreased. Moreover, while the total number of sperm in the ejaculate increased, the number of insemination doses obtained from a single ejaculate were higher. CONCLUSION: The volume of ejaculate has little impact on the occurrence of morphological abnormalities and the size of sperm cells. Ejaculate volume is important for the shape of the sperm cells.